2022
DOI: 10.31234/osf.io/72myr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychometric properties of the General Risk Propensity Scale (GRiPS) in a Brazilian sample

Abstract: Risk propensity is the probability of individuals engaging in activities in which there is variability in possible outcomes. In a recent effort to measure general risk-taking propensity, Zhang, Highhouse and Nye (2018) developed and evaluated the General Risk Propensity Scale (GRiPS) using a total sample of 1,523 participants across five studies. The authors found construct validity evidence via the internal structure of item responses and convergence with other self-report measures of risk propensity. They al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(22 reference statements)
0
2
1
Order By: Relevance
“…In terms of factorial validity, the EFA-to-CFA approach to explore the best-tting model of the GRiSP suggested that the original one-factor was replicated in this study, except for two items that were removed (item 4 "I would take a risk even if it meant I might get hurt", and item 5 "Taking risks is an important part of my life"). In contrast to our ndings, Porfírio et al [29] were able to replicate the unidimensional model with all eight items loading on a single latent variable in a Brazilian sample of adults from the general population. These variations in factor structure might be explained by cultural variations in people's perceptions of, and attitudes toward, engaging in risky behaviors [31].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In terms of factorial validity, the EFA-to-CFA approach to explore the best-tting model of the GRiSP suggested that the original one-factor was replicated in this study, except for two items that were removed (item 4 "I would take a risk even if it meant I might get hurt", and item 5 "Taking risks is an important part of my life"). In contrast to our ndings, Porfírio et al [29] were able to replicate the unidimensional model with all eight items loading on a single latent variable in a Brazilian sample of adults from the general population. These variations in factor structure might be explained by cultural variations in people's perceptions of, and attitudes toward, engaging in risky behaviors [31].…”
Section: Discussioncontrasting
confidence: 99%
“…These ndings indicate that both scales measure the RTP construct in the same way across males and females, and that inferences based on gender differences on the variances or means of GRiPS and R-1 latent scores are likely not confounded by measurement bias [60, 61]. Consistently, measurement invariance of the GRiPS was demonstrated in the Brazilian sample [29]. Establishing this psychometric property is of high relevance, given that gender comparisons represent a key research interest in the area of risk-propensity [62].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation